Sensitivity of accelerator-based neutrino experiments to neutrino-dark matter interaction: Elko as a viable dark matter candidate. (1st October 2022) - Moura, C. A.; Kamiya, F.; Duarte, L.; Dias, M.; Hoff da Silva, J. M.
Abstract: We analyze the potential of accelerator-based neutrino experiments, such as the Deep Underground Neutrino Experiment, to constrain a five-dimensional operator mediating a beyond standard model interaction between a mass-dimension-one fermion field, labeled elko, and neutrino. We identify the parameter space where elko is a viable dark matter candidate.